Optimizing Clinical Use of Biologics in Orthopaedic Surgery: Consensus Recommendations From the 2018 AAOS/NIH U-13 Conference. Issue 2 (15th January 2019) - Chu, Constance R.; Rodeo, Scott; Bhutani, Nidhi; Goodrich, Laurie R.; Huard, Johnny; Irrgang, James; LaPrade, Robert F.; Lattermann, Christian; Lu, Ying; Mandelbaum, Bert; Mao, Jeremy; McIntyre, Louis; et al.
Abstract : Concern that misinformation from direct-to-consumer marketing of largely unproven "biologic" treatments such as platelet-rich plasma and cell-based therapies may erode the public trust and the responsible investment needed to bring legitimate biological therapies to patients have resulted in calls to action from professional organizations and governing bodies. In response to substantial patient demand for biologic treatment of orthopaedic conditions, the American Academy of Orthopaedic Surgeons convened a collaborative symposium and established a consensus framework for improving and accelerating the clinical evaluation, use, and optimization of biologic therapies for musculoskeletal diseases. The economic and disease burden of musculoskeletal conditions is high. Of the various conditions discussed, knee osteoarthritis was identified as a "serious condition" associated with substantial and progressive morbidity and emerged as the condition with the most urgent need for clinical trial development. It was also recognized that stem cells have unique characteristics that are not met by minimally manipulated mixed cell preparations. The work group recommended that minimally manipulated cell products be referred to as cell therapy and that the untested and uncharacterized nature of these treatments be clearly communicated within the profession, to patients, and to the public. Minimum standards for product characterization and clinical research should also be followed. A framework for developing clinical trials related to knee OA was agreed upon. In addition to recommendations for development of high-quality multicenter clinical trials, another important recommendation was that physicians and institutions offering biologic therapies commit to establishing high-quality patient registries and biorepository-linked registries that can be used for postmarket surveillance and quality assessments.